2005
DOI: 10.1021/jm050618p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Activity, and Preliminary Pharmacokinetic Evaluation of Analogues of a Phosphosulfomannan Angiogenesis Inhibitor (PI-88)

Abstract: The phosphosulfomannan 1 (PI-88) is a mixture of highly sulfated oligosaccharides that is currently undergoing clinical evaluation in cancer patients. As well as its anticancer properties, 1 displays a number of other interesting biological activities. A series of analogues of 1 were synthesized with a single carbon (pentasaccharide) backbone to facilitate structural characterization and interpretation of biological results. In a fashion similar to 1, all compounds were able to inhibit heparanase and to bind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 30 publications
(89 reference statements)
1
70
0
Order By: Relevance
“…It has been reported that inhibiting the expression of HPA can lead to inhibition of tumor invasiveness, metastasis and angiogenesis [9,10] . However, because of the multiple biologic activities of these compounds, the mechanism of their antitumor activity and its relation to HPA inhibition are not straightforward [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that inhibiting the expression of HPA can lead to inhibition of tumor invasiveness, metastasis and angiogenesis [9,10] . However, because of the multiple biologic activities of these compounds, the mechanism of their antitumor activity and its relation to HPA inhibition are not straightforward [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the multiple biologic activities of these compounds, the mechanism of their antitumor activity and its relation to HPA inhibition are not straightforward [8][9][10][11] . Moreover, the pleiotropic interactions of these compounds with the ECM and the cell surface might produce nonspecific and undesirable effects [8][9][10][11] . Thus, novel approaches are needed to reduce the role of HPA in cancer progression [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported angiogenic factors are FGF2 and VEGF. For example, the HS mimetic PI-88, which is in phase II clinical trials for several types of cancer (42), inhibits angiogenesis by strongly binding to FGF1, FGF2, and VEGF (15,43). HS was also reported to bind to the BMP proteins to interfere with BMP/Smad signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their negative charge, they bind multiple functional proteins, including proangiogenic factors such as VEGF and FGF2, and thus mediate angiogenic signaling (14). HS mimetics such as PI-88 can inhibit angiogenesis via disrupting those interactions between HS and growth factors (15). TGF-␀ family proteins can also bind HS chains.…”
Section: Hepatocellular Cancer (Hcc)mentioning
confidence: 99%
“…PI-88 is a mimetic of heparan sulfate, yet it possesses decreased anticoagulant properties compared with heparin and may therefore be more favorable as an adjunct therapy due to decreased risk of hemorrhagic complications. This oligosaccharide does, however, have limitations; phase I studies indicated that intravenous administration at 2.28 mg/kg/day for 2 weeks resulted in immune-mediated thrombocytopenia in some patients (23), and a short half-life of approximately 1 h has been measured in rats (16), although improvements in pharmacokinetic properties of sulfated oligosaccharides of this type are possible (16). These issues, together with the likelihood that such compounds would be effective only with parenteral administration, will need to be addressed if such a carbohydrate-based drug is to be developed as a novel antimalarial therapy.…”
mentioning
confidence: 99%